The Development of SMP Statistics Learning Devices Using Realistic Mathematic Education Approach to Develop Students Mathematical Literacy Ability - Kartini, Kartini; Baroqah, Lailatul; Siregar, Syarifah Nur; Maimunah, Maimunah (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study is aimed at producing a learning tool for statistics of junior high school using realistic mathematics education approach which includes valid and practical lesson plans (RPP) and students worksheets (LKS) to develop mathematical literacy skills. This development research refers to the 4-D development model from Thiagarajan which consists of define, design, development, and disseminate stages. The test subjects were seventh grader students of SMP Negeri 8 Pekanbaru. The data ware obtained using validation sheets by experts and students response questionnaire sheets. It is found that the result of expert validation for RPP is 3.84 (very valid) and for LKS 3.52 (very valid). The students worksheet has suited the practicality requirements with the percentage of student responses reaching 88.57%. It can be concluded that the RPP and LKS have fulfilled valid and practical requirements.